C4 Marking Schemes

Download C4 Marking Schemes

Post on 27-Nov-2014

327 views

Category:

Documents

2 download

Embed Size (px)

DESCRIPTION

C4 solomon press answers

TRANSCRIPT

<p>C41</p> <p>SERIESa = 1 + (1)x + b = 1 + ( 1 )x + 2 =1+1 2( 1)( 2) 2 3</p> <p>Answers - Worksheet Ax2 +( 1)( 2)( 3) 3 2</p> <p>x3 + </p> <p>= 1 x + x2 x + x</p> <p>( 1 )( 1 ) 2 ( 1 )( 1 )( 3 ) 2 2 2 x + 2 32 2 2 1 2 1 x + 16 x3 + 8 ( 3)( 4) 2 2 3</p> <p>x3 + </p> <p>c = 2[1 + (3)x + d = 1 + ( 2 )x + 3 =1+2 3</p> <p>x2 +</p> <p>( 3)( 4)( 5) 3 2</p> <p>x3 + ]</p> <p>= 2 6x + 12x 20x + x1</p> <p>( 2 )( 1 ) 2 ( 2 )( 1 )( 4 ) 3 3 3 x + 3 32 3 2 1 2 4 x + 81 x3 + 9 ( 1 )( 2 ) 3 3 2</p> <p>x3 + </p> <p>e = (1 x) 3 = 1 + ( 1 )(x) + 3 =11 3</p> <p>(x)2 +</p> <p>( 1 )( 2 )( 5 ) 3 3 3 3 2</p> <p>(x)3 + </p> <p>x</p> <p>1 9</p> <p>x2 </p> <p>5 81</p> <p>x3 + ( 2)( 3) 2</p> <p>f = (1 + x)2 = 1 + (2)x + = 1 2x + 3x2 4x3 + g = =1 4 1 4</p> <p>x2 +</p> <p>( 2)( 3)( 4) 32</p> <p>x3 + ( 4)( 5)( 6) 3 2</p> <p>(1 x)4 = +x+5 2</p> <p>1 4</p> <p>[1 + (4)(x) +</p> <p>( 4)( 5) 2</p> <p>(x)2 +</p> <p>(x)3 + ]</p> <p>x2 + 5x3 + = 3[1 + ( 1 )(x) + 29 8 ( 1 )( 3 ) 2 2 2</p> <p>h = 3(1 x) =3+ 23 2</p> <p>1 2</p> <p>(x)2 +</p> <p>( 1 )( 3 )( 5 ) 2 2 2 3 2</p> <p>(x)3 + ]</p> <p>x+</p> <p>x2 +</p> <p>15 16</p> <p>x3 + (2x)3 + valid for | x | &lt; (3x)3 + 1 3 1 2</p> <p>a = 1 + ( 1 )(2x) + 2 =1+x1 2</p> <p>x2 +</p> <p>( 1 )( 1 ) ( 1 )( 1 )( 3 ) 2 2 2 (2x)2 + 2 32 2 2 1 3 x + , | 2x | &lt; 1 2 ( 1)( 2) 2 3</p> <p>b = 1 + (1)(3x) +</p> <p>(3x)2 +</p> <p>( 1)( 2)( 3) 3 2</p> <p>= 1 + 3x + 9x2 + 27x + , | 3x | &lt; 1 c = 1 + ( 1 )(4x) + 2 d = 1 + (3)( 1 x) + 2 =13 2 ( 1 )( 3 ) 2 2 2 3</p> <p> valid for | x | &lt; (4x)3 + </p> <p>(4x)2 +</p> <p>( 1 )( 3 )( 5 ) 2 2 2 3 2</p> <p>= 1 + 2x + 6x2 + 20x + , | 4x | &lt; 13 2</p> <p> valid for | x | &lt; ( 1 x)3 + 2</p> <p>1 4</p> <p>x+</p> <p>x2 </p> <p>( 3)( 4) 2 5 3 x + 4</p> <p>( 1 x)2 + 2</p> <p>( 3)( 4)( 5) 3 2</p> <p>, | 1 x | &lt; 1 2( 1 )( 2 )( 5 ) 3 3 3 3 2</p> <p> valid for | x | &lt; 2 (6x)3 + valid for | x | &lt; ( 1 x)3 + 41 6</p> <p>e = 1 + ( 1 )(6x) + 3 = 1 2x 4x2 f = 1 + (4)( 1 x) + 4 =1x+5 8</p> <p>( 1 )( 2 ) 3 3 2 40 3 x + 3</p> <p>(6x)2 +</p> <p>, | 6x | &lt; 1 x)2 + |1 x| &lt; 1 4</p> <p>x2 </p> <p>( 4)( 5) 1 (4 2 5 3 x + , 16</p> <p>( 4)( 5)( 6) 3 2</p> <p> valid for | x | &lt; 4 (2x)3 + valid for | x |</p>

Recommended

View more >